2016
DOI: 10.1016/j.porgcoat.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of electrochemical noise measurement as a tool for evaluation of organic coatings

Abstract: The simplicity of measuring equipment and versatility of data analysis makes electrochemical noise measurement an ideal technique for acquiring electrochemical information about the corrosion behavior of a painted metal relatively quickly. Hence the method has great potential for use in the laboratory as well as in field situations. However, special care must be taken in choosing data acquisition parameters, reference electrodes and symmetry of electrodes in order to achieve reproducible measurements. These ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 107 publications
(151 reference statements)
0
38
0
Order By: Relevance
“…Consequently, the application of EN has gained growing attention in corrosion research [24,25]. In recent decades, studies on EN analysis of polymer coated metals also have been reported widely [3,26,27]. However, two issues restrict its application in the field.…”
Section: Electrochemical Noise Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the application of EN has gained growing attention in corrosion research [24,25]. In recent decades, studies on EN analysis of polymer coated metals also have been reported widely [3,26,27]. However, two issues restrict its application in the field.…”
Section: Electrochemical Noise Methodsmentioning
confidence: 99%
“…Subsequently, the oxygen and the dissolved ions penetrate into the coating; thus, the corrosive medium solution forms on the coating/metal interface, resulting in the occurrence of electrochemical reactions [2]. The rate determining step in controlling the electrochemical reaction should be the diffusion rate of ions through the coating [3]. The locations of anode and cathode areas are separate on the surface of metal substrate, due to the inhomogeneity of transport of the corrosive medium (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…From the results above, a certain proportion of impedance between WEs can affect the EN measurement accordingly. However, the inhomogeneous structure of coatings causes a variation of physical properties from the microscopic angle, with a random distribution across the film [14]. Due to the presence of micro defects and inconsistency of physical and/or chemical properties, several localized corrosion of metal or localized damage of coating can significantly change the impedance performance.…”
Section: En Time Records After Remarkable Corrosion Of Metal Substratementioning
confidence: 99%
“…It is difficult to meet this requirement in the field, especially for the coating/metal system. Two separate but identical coated metals are rare to find in engineering application, in view of the geometric structure of materials is often uncontrollable [14]. In other words, there may be an asymmetry of working electrodes in the EN measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation